2014
DOI: 10.1002/chem.201304448
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Aromatic Interactions for β‐Peptide Foldamer Helix Stabilization: A Significant Design Element

Abstract: Tetrameric H10/12 helix stabilization was achieved by the application of aromatic side-chains in β-peptide oligomers by intramolecular backbone-side chain CH-π interactions. Because of the enlarged hydrophobic surface of the oligomers, a further aim was the investigation of the self-assembly in a polar medium for the β-peptide H10/12 helices. NMR, ECD, and molecular modeling results indicated that the oligomers formed by cis-[1S,2S]- or cis-[1R,2R]-1-amino-1,2,3,4-tetrahydronaphthalene-2-carboxylic acid (ATENA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…Among the secondary structures, hydrogen bonding between carbonyl oxygen and the amino group of every third residue in the helical turn stabilizes an α-helix (each helical turn consisting of 3.6 amino acid residues) while βsheets originate with hydrogen bonding between two or more β-strands (along which, the backbone of the peptide stretches) (Kulkarni et al, 2019). The self-association phenomenon of aromatic side-chains in β-peptide oligomers supports the helical secondary structure formed by intramolecular backbone-side chain CH-π interactions and yields large vesicles due to the gain in the hydrophobic area (Mándity et al, 2014). In a study, Sarkar et al (2015) have also demonstrated the effect of solvent interactions on the folding pattern resulting in a change in initial helical conformation and structural diversity of short aromatic γpeptides.…”
Section: Secondary Structural Conformationsmentioning
confidence: 99%
“…Among the secondary structures, hydrogen bonding between carbonyl oxygen and the amino group of every third residue in the helical turn stabilizes an α-helix (each helical turn consisting of 3.6 amino acid residues) while βsheets originate with hydrogen bonding between two or more β-strands (along which, the backbone of the peptide stretches) (Kulkarni et al, 2019). The self-association phenomenon of aromatic side-chains in β-peptide oligomers supports the helical secondary structure formed by intramolecular backbone-side chain CH-π interactions and yields large vesicles due to the gain in the hydrophobic area (Mándity et al, 2014). In a study, Sarkar et al (2015) have also demonstrated the effect of solvent interactions on the folding pattern resulting in a change in initial helical conformation and structural diversity of short aromatic γpeptides.…”
Section: Secondary Structural Conformationsmentioning
confidence: 99%
“…[22] Finally,t his C À Hc arbamoylation method was applied to the synthesis of the enantiopure free b-lactam 4ac and baminoacid 5ac.T he latter,which was previously obtained by enzymatic resolution, is of high interest for the synthesis of bpeptides (Scheme 5). [23] Commercially available enantiopure tetrahydronaphthylamine 3ac was converted into carbamoyl chloride 1ac,w hich underwent CÀHc arbamoylation under the optimal COgen conditions to give TMB-protected blactam 2ac in 82 %y ield. Persulfate-mediated oxidative cleavage provided b-lactam 4ac,w hich underwent acidic hydrolysis to give (+ +)-5ac in very good overall yield (64 %for 5steps).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Although levels of enantioselectivity higher than 92:8 could not be reached, this result constitutes ap roof-of-concept enantioselective synthesis of b-lactams through the desymmetrization of unactivated methyl groups,w hich is to date unprecedented. [23] Commercially available enantiopure tetrahydronaphthylamine 3ac was converted into carbamoyl chloride 1ac,w hich underwent CÀHc arbamoylation under the optimal COgen conditions to give TMB-protected blactam 2ac in 82 %y ield. [22] Finally,t his C À Hc arbamoylation method was applied to the synthesis of the enantiopure free b-lactam 4ac and baminoacid 5ac.T he latter,which was previously obtained by enzymatic resolution, is of high interest for the synthesis of bpeptides (Scheme 5).…”
Section: Angewandte Chemiementioning
confidence: 99%